Modern information and communication technologies in management: characteristics of the electronic course for masters - Totska, Olesia Leontiivna (Волинський національний університет імені Лесі Українки, 2025)
The distance learning course "Modern information and communication technologies in management" for masters is described.
Keywords: information and communication technologies; management